Detection of pathogens in Boidae and Pythonidae with and without respiratory disease. (2nd March 2013) - Schmidt, V.; Marschang, R. E.; Abbas, M. D.; Ball, I.; Szabo, I.; Helmuth, R.; Plenz, B.; Spergser, J.; Pees, M.
Abstract : Respiratory diseases in boid snakes are common in captivity, but little information is available on their aetiology. This study was carried out to determine the occurrence of lung associated pathogens in boid snakes with and without respiratory signs and/or pneumonia. In total, 80 boid snakes of the families Boidae (n = 30) and Pythonidae (n = 50) from 48 private and zoo collections were included in this survey. Husbandry conditions were evaluated using a detailed questionnaire. All snakes were examined clinically and grouped into snakes with or without respiratory signs. Tracheal wash samples from all snakes were examined bacteriologically as well as virologically. All snakes were euthanased, and a complete pathological examination was performed. Respiratory signs and pneumonia were detected more often in pythons than in boas. An acute catarrhal pneumonia was diagnosed more often in snakes without respiratory signs than in snakes with respiratory signs, which revealed fibrinous and fibrous pneumonia. Poor husbandry conditions are an important trigger for the development of respiratory signs and pneumonia. Different bacterial pathogens were isolated in almost all snakes with pneumonia, with Salmonella species being the most common. Ferlavirus (formerly known as ophidian paramyxovirus)‐RNA was detected only in pythons. Inclusion body disease was rarely seen in pythons but often in boas. Adenovirus and Mycoplasma were other pathogens that were diagnosed in single snakes with pneumonia. In living boid snakes with respiratory signs, tracheal wash samples were found to be a useful diagnostic tool for the detection of viral and bacterial pathogens.